الصعوبات التي تواجه الباحث الجزائري في عملية النشر في المجلات العلمية الجزائرية المصنفة - سلامى، خديجة; جرودي، مريم; يسعد، ليلى محمد (جامعة العربي التبسي تبسة - مخبر الدراسات الإنسانية والأدبية, 2022)
يعاني المجتمع الجزائري من صعوبات ومشاكل جمة منها ما ورثها عن الاستعمار والانتداب الغربي، ومنها راجع إلى طريقة تسيير هذه الأوطان في ظل أنظمة معظمها ديكتارورية لا تهتم بشؤون أوطانها بل بشؤون حكمها واستمراريته. وهذه الصعوبات والعراقيل لا يخلو أي مجال منها سواء في الجانب الاقتصادي والتربوي والاجتماعي الثقافي والبحث العلمي، ويعتبر النشر العلمي جزء مهم من هذا الأخير له مشاكله وعراقيله منها ما هو مرتبط بسياسة البلد (تسييسه) حيث يتم نشر ما يروق ويخدم النظام السياسي، ومنها ما هو مرتبط بمسؤولي هذه المؤسسة العلمية المتشبعين بثقافة معينة فهم يعيقون أي نشر لا يتوافق مع أيديولوجياتهم، بالإضافة إلى المحاباة والقرابة والعلاقات الشخصية والمصالح المشتركة في النشر ومن جهة أخرى اعتماد بعض المجلات فرض رسوم في النشر تثقل كاهل الباحث وتلزمه بدفعها، وكذا المعيقات الإدارية والتنظيمية كتأخر الرد بنتيجة التحكيم أو الرفض وعدم تبريره أو الرفض الآلي نتيجة لعدم احترام قالب المجلة وعليه سوف نتطرق في هذا البحث إلى ابرز المعيقات التي تعيق الباحث في مجال النشر العلمي. Algerian society suffers from many difficulties and problems, some of which are inherited from colonialism and Western mandate, and from them refer to the way these countries are run under regimes, most of which are dictatorial, not concerned with the affairs of their homelands, but rather with the affairs of their rule and its continuity. Economic, educational, social, cultural, and scientific research, and scientific publishing is an important part of the latter. It has its problems and obstacles, including what is related to the country’s policy (politicization), whereby what is published and serves the political system, including what is related to the officials of this scientific institution imbued with a certain culture, they hinder any publication that does not conform to their ideologies; In addition to favoritism, kinship, personal relationships, and common interests in publishing, on the other hand, the adoption of some magazines imposing publishing fees that burden the researcher and obligate him to pay them, as well as administrative and organizational obstacles such as delaying the response as a result of arbitration, rejection and not justifying it, or automatic rejection as a result of not respecting the template. Therefore, in this research, we will address the most prominent obstacles that hinder the researcher in the field of scientific publishing.
Keywords: البحوث العلمية -- المجلات العلمية -- النشر العلمي -- المؤسسات الجامعية -- الجزائر